2019
DOI: 10.1590/1678-4162-10297
|View full text |Cite
|
Sign up to set email alerts
|

Comparação da qualidade seminal de caprinos das raças Canindé e Alpina Britânica no Nordeste brasileiro

Abstract: RESUMO O estudo objetivou avaliar a qualidade seminal de caprinos das raças Canindé (autóctone) e Alpina Britânica (exótica) no Nordeste brasileiro. O experimento foi realizado nos períodos de julho a setembro dos anos de 2015 e 2016. As coletas seminais foram realizadas com auxílio de vagina artificial, de machos das raças Canindé (n = 4) e Alpina Britânica (n = 7). Após a coleta, o sêmen foi avaliado quanto a: volume (ml), concentração (sptz/ml), motilidade (%) e vigor (1-5). Em seguida, diluído em ACP-101c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In other studies using ACP® as cryopreservation medium with the addition of egg yolk did not show statistical difference regarding the post-thawing seminal quality (Câmara et al, 2019).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In other studies using ACP® as cryopreservation medium with the addition of egg yolk did not show statistical difference regarding the post-thawing seminal quality (Câmara et al, 2019).…”
Section: Discussionmentioning
confidence: 70%
“…Several studies have reported low values in the goat species for post-thawing progressive motility: 22 % in native and 6% in British Alpine goats (Câmara et al, 2019). This is a very important sperm parameter in reproducer choice and also in the assessments of semen freezing protocols (Câmara et al, 2019;Santiago-Moreno et al, 2017).…”
Section: Discussionmentioning
confidence: 99%